Introduction to Basic and Applied Clinical Pharmacokinetics Using Interactive Lecturing and Case-Based Self-learning Modules - Michael Lee (Association of American Medical Colleges, 2015)
Abstract Introduction This interactive lecture and self-learning module (SLM) on pharmacokinetics was designed to transition students towards independent application of basic pharmacokinetics to clinical cases. The interactive lecture session and the SLM are intended to be used in tandem, but can also be used as separate entities depending on curricular needs and learner background. Both faculty and student versions of the interactive lecture and the SLM are included along with a 10-question formative quiz with answers. Methods The interactive lecture is covered over two back-to-back 50-minute classroom sessions on a Friday morning. The SLM is released later in the afternoon for the students to work on over the weekend. The following Monday, a 30-minute wrap-up session is convened where the instructor writes out all of the problems and answers with direction from the students, using either a dry erase board or an electronic overhead projector for all students to view. The wrap-up session is conducted in a traditional classroom setting and no additional facilitators are necessary other than the principle instructor. Results For the past 4 years, this resource has been successfully deployed in the first year of the University of Central Florida College of Medicine's cellular function and medical genetics course. Following the deployment of this module, formative feedback was solicited from students asking them to rank the effectiveness of the learning materials and provide their comments. Overall, students rated the effectiveness of the learning materials highly, as a 4.75 out of 5 (N = 119). Discussion The formative quiz was released concomitantly with the SLM and the students had the weekend to complete it. Surprisingly, not all students took the formative quiz (only around 68%) and the student motives for taking the quiz differed markedly. For example, some students reported using the formative quiz as a way to assess what they did or did not know before studying or working on the SLM. Other students reported taking the quiz after studying and completing the SLM in order to gauge their learning. Because of this, the statistical data from the formative quizzes, as it is currently deployed, is not helpful in assessing the effectiveness of the interactive lecture or SLM.